LOCAL WISDOM OF FARMERS IN MEETING OF LOCAL FOOD - WA KUASA; USMAN RIANSE; WEKA WIDAYATI; DASMIN SIDU; Weka GUSMIARTY ABDULLAH; ZULFIKAR LA ZULFIKAR; LA ODE SYUKUR; ILMA SARIMUSTAQIYMA RIANSE (International Journal of Sustainable Tropical Agricultural Sciences (IJSTAS), 2015)
Abstract.The objective of this study were to describe types and form of local wisdom in meeting of local food and its implementation compare with the condition of 30 years ago. Populations of this study were farmers who have farming experience more than 30 years. Qualitative analysis was be used in this study. The study results showed that there were some types of farmer’s local wisdoms, consist of land opening, land preparing, cultivation, harvesting, and processing of farm products. Types of local wisdom such as agriculture systems, and ritual ceremonies. An agriculture system in land preparing was slash and burn system, in the procedure of planting and maintenance of plants in the form of a system of rotation and intercropping, while the processing of agricultural product is done by prescription obtained hereditary. Ritual ceremonial among others; Kasalasa, Kaago-ago, and Kasambuwite. Local wisdom that are still maintained in land preparing by slash and burn system, in cultivation with rotation and intercropping system, and in processing of agricultural product into comestible durable. Traditional rituals began experiencing fading due to the times and increased demands of life.Keyword: local wisdom, farmers, local food